Students' Metacognitive Awareness in Mathematics Learning - Telaumbanua, Yakin Niat; Syahputra, Edi; Surya, Edi (Academy of Education Journal, 2024)
Understanding students' level of metacognitive awareness in the process of learning mathematics can assist them in developing their metacognitive abilities and enhancing their mathematical comprehension. Through this research, students' metacognitive awareness is analyzed so that educators can design and develop more effective teaching strategies to address students' difficulties in solving mathematical problems. This study is a descriptive quantitative research conducted to describe the metacognitive awareness of students in the Mathematics Education Study Program at the University of Nias involving a total of 58 students. The data collection technique employed in this research is through the Metacognitive Awareness Inventory (MAI) questionnaire. The research findings indicate that metacognitive awareness measured from the cognitive regulation aspect obtained higher scores compared to metacognitive knowledge. In terms of metacognitive knowledge aspect, the highest statement values related to procedural knowledge processes, indicating that students have specific goals for each strategy they use, while the lowest values were found in declarative knowledge processes, stating that students are adept at organizing information. The smallest overall percentage value in the assessment of metacognitive awareness is associated with statements such as slowing down when finding important information and using pictures or diagrams to aid understanding while learning.